2011
DOI: 10.1007/s10900-011-9511-2
|View full text |Cite
|
Sign up to set email alerts
|

Early Community Contexts, Race/Ethnicity and Young Adult CVD Risk Factors: The Protective Role of Education

Abstract: Using a sample of 13,500 adolescents (53% female and 47% male) who participated in all four waves of the National Longitudinal Study of Adolescent Health, this study used multilevel regression to examine the influence of early structural community adversity (as measured by rates of community poverty, single-parent headed families, and two indicators of employment) and racial/ethnic status on cardiovascular disease (CVD) risk factors of young adults (systolic blood pressure, diastolic blood pressure, and mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…Using Add Health data, Nicholson and Browning (12) found higher risk of obesity among women aged 18-26 years who lived in disadvantaged neighborhoods as adolescents (OR = 1.22, 95% CI: 1.11, 1.35). Also using Add Health, Wickrama et al (69) find a positive association between wave-1 school-district disadvantage and higher blood pressure (for systolic blood pressure, b = 3.2, P < 0.05; for diastolic blood pressure, b = 3.63, P < 0.001). Estimates from the Panel Study of Income Dynamics indicated that adolescents who lived in neighborhoods with poverty rates between 10%-20% had significantly higher risks for self-reported diabetes (hazard ratio = 1.70, 95% CI: 1.07, 2.70) by age 50 years than did those from nonpoor neighborhoods (70).…”
Section: Resultsmentioning
confidence: 99%
“…Using Add Health data, Nicholson and Browning (12) found higher risk of obesity among women aged 18-26 years who lived in disadvantaged neighborhoods as adolescents (OR = 1.22, 95% CI: 1.11, 1.35). Also using Add Health, Wickrama et al (69) find a positive association between wave-1 school-district disadvantage and higher blood pressure (for systolic blood pressure, b = 3.2, P < 0.05; for diastolic blood pressure, b = 3.63, P < 0.001). Estimates from the Panel Study of Income Dynamics indicated that adolescents who lived in neighborhoods with poverty rates between 10%-20% had significantly higher risks for self-reported diabetes (hazard ratio = 1.70, 95% CI: 1.07, 2.70) by age 50 years than did those from nonpoor neighborhoods (70).…”
Section: Resultsmentioning
confidence: 99%
“…The fact that nativity differences are greater among the less educated group suggests that educational attainment is a major moderating factor [34] and social determinant of race-ethnic and nativity disparities in cardiovascular health behaviors and outcomes. Education was a significant predictor of CV health behaviors and health status measures, even controlling for housing tenure, employment status, family income, and other SES measures.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the salience of observed psychosocial resources may vary across ethnic groups. For example, Wickrama, O’Neal, and Lott (2012) have shown that African American young adults do not accrue the same health benefits of education (lower cardiovascular disease [CVD] risk) as Whites. Thus, we expect the mediating role of psychosocial resources to vary across racial/ethnic groups.…”
Section: The Theoretical Framework and Hypothesesmentioning
confidence: 99%